Peran Sosial Komite Sekolah dalam Penanaman Nilai-Nilai Demokrasi di Sekolah - Suwarno, Suwarno; Bramantyo, Rizki Yudha (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2020)
The purpose of this study describes: 1) the social role of the school committee in improving the quality of education, and 2) the form of instilling democratic values ​​in schools through cooperation of school and school committee. This research uses a descriptive study with a qualitative research approach. Data were collected using participatory observation techniques, in-depth interviews, and documentation. Data analysis using four steps of qualitative research includes data collection, data reduction, data classification, and drawing conclusions. Based on the process of data collection and analysis, it can be concluded that the school committee's social role is as a liaison between the school and the community in all matters. School committees can instill democratic values ​​in schools through sharing meetings since the formation of the board, program formulation, implementation, monitoring, and program evaluation all emphasize deliberation to reach consensus.